2017
DOI: 10.1159/000480705
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening: What Is the Population's Opinion

Abstract: Background: Colorectal cancer (CRC) is the first cause of death by cancer in Portugal and mortality has been increasing in the last 30 years. Materials and Methods: During a raising awareness campaign performed by our Gastroenterology Department, in Setúbal, Portugal, an anonymous written questionnaire was developed and presented in order to evaluate the population's knowledge and attitude regarding CRC screening. Results: The following results were reported: 140 persons; mean age 54.6 years; 61.4% women; 22.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
1
11
2
5
Order By: Relevance
“…However, no statistically significant relationship was found between gender and undergoing a CRC screening test according to the logistic regression analysis conducted (OR = 0.438, 95% CI 0.164–1.169). Some other studies have reported higher rates for female participation than males for CRC screening, similar to our results (Arnold, Rademaker, Liu, & Davis, ; Teixeira et al, ; Yılmaz et al, ), while there are also studies with the opposite finding (So et al, ). We believe our result is partly due to the higher rate of family health centre visits to use healthcare services by women.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, no statistically significant relationship was found between gender and undergoing a CRC screening test according to the logistic regression analysis conducted (OR = 0.438, 95% CI 0.164–1.169). Some other studies have reported higher rates for female participation than males for CRC screening, similar to our results (Arnold, Rademaker, Liu, & Davis, ; Teixeira et al, ; Yılmaz et al, ), while there are also studies with the opposite finding (So et al, ). We believe our result is partly due to the higher rate of family health centre visits to use healthcare services by women.…”
Section: Discussionsupporting
confidence: 91%
“…The study data were collected with the ‘Data Collection Form' created by the authors after reviewing the relevant literature (Bocci, Troiano, Messina, Nante, & Civitelli, ; Harewood et al, ; Teixeira et al, ; Wong et al, ) and the ‘Health Belief Model Scale for Protection from Colorectal Cancer (HBMSPCC)'. We used 17 questions related to the socio‐demographic characteristics (such as age, gender, educational level, marital status, perceived income, social security coverage, personal habits, chronic diseases, history of cancer, body mass index [BMI]) and 15 questions related to their CRC risk knowledge and behaviour (such as those related to CRC risk, symptoms and screening status) for a total of 32 questions in the data collection form.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of GTT uptake among males in MMR families as compared with females could be a possible explanation . Furthermore, studies showed that cancer screening may be perceived as a taboo subject . This attitude could complicate the messenger task, leading to avoidance behaviors both in probands and family members.…”
Section: Discussionmentioning
confidence: 99%
“…In the current edition of GE -Portuguese Journal of Gastroenterology, Teixeira et al [7], from the Centro Hospitalar de Setúbal in Portugal, try to fill in this gap and report their valuable experience and the data gathered during a local awareness campaign designed and conducted by gastroenterologists and associated health professionals. Their aim was mainly to raise awareness by direct interaction with the public but Colorectal cancer (CRC) is the most frequent and lethal cancer in Portugal [1], even though it is well established that screening leads to a significant reduction in both CRC-specific mortality [2] and incidence [3,4].…”
mentioning
confidence: 99%